2015
DOI: 10.32400/gc.10.2.8371.2015
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Psak No. 45 Pada Gereja Gmim Bukit Zaitun Walian Dua

Abstract: Disclosure of financial statements of the Church so important that financial accountability becomes clear, and can increase the confidence of donors and people who have given charity to the Church to manage the fund. Demands for accountability are adequate, especially for non-profit organizations of the Church can be overcome by applying general standards that apply in Indonesia, PSAK No. 45 on financial reporting nonprofits. The purpose of this study was to determine how the Financial Statements GMIM Olivet C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
4
1
3
Order By: Relevance
“…The results of this study are not in line with the research conducted by Kumambow et al (2015), which showed that the non-profit organization that implemented it was the GMIM Church Bukit Zaitun Walian Dua. It compiled the financial statements based on the church's order, in which the financial statements were made in the form of a budget realization report that contained the income and expenditure of the church during the year.…”
Section: Activity Report On Political Partiescontrasting
confidence: 95%
See 3 more Smart Citations
“…The results of this study are not in line with the research conducted by Kumambow et al (2015), which showed that the non-profit organization that implemented it was the GMIM Church Bukit Zaitun Walian Dua. It compiled the financial statements based on the church's order, in which the financial statements were made in the form of a budget realization report that contained the income and expenditure of the church during the year.…”
Section: Activity Report On Political Partiescontrasting
confidence: 95%
“…A non-profit organization is an organization that has, as its main objective, to support an issue or matter in attracting public attention to a non-commercial purpose, without any consideration of the problems that are for-profit (monetary). Non-profit organizations include churches, public schools, public charities, hospitals and public clinics, political organizations, community assistance in legislation, voluntary service organizations, trade unions, professional associations, research institutes, museums, and several government officials (Kumambow, 2015). Non-profit organizations have the following characteristics: a.…”
Section: Non-profit Organizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Accounting practices at that time were determined from annual reports and evaluated based on the criteria and statements of the accounting profession in accordance with the reporting practices desired by the Roman Catholic church at that time [1]. Research on the financial accounting practices of the Church in Indonesia has been carried out [6] [7] [8] [9] [10] [11] [12] [13] [14] [15], discussing the general application of Church accounting which employs PSAK No. 45.…”
Section: Introductionmentioning
confidence: 99%